Voices in the theater - Santos, A.S.; Banzuelo Lester (Quezon City Shepherd's Voice Publications, Incorporation, 2015)
Voices in the theater is the first installment of A. S. Santos's three-book Young Adult Paranormal Romance. Follow Sam and her friends in the Student Paranormal Research Group as they encounter bizarre and often dangerous supernatural occurrences, battle demons both spiritual and psychological, and navigate adolescence and young love.
Prologue -- Chapter 1: Reasons -- Chapter 2: Truths and half-truths -- Chapter 3: Do you hear them? -- Chapter 4: Names and places -- Chapter 5: The little theater -- Chapter 6: Voices in our heads -- Chapter 7: Secrets -- Chapter 8: Stories -- Chapter 9: Unfinished business -- Chapter 10: Frequencies -- Chapter 11: Michael -- Chapter 12: Torn -- Chapter 13: Guardian -- Chapter 14: Love from strange places -- Chapter 15: The reveal -- Chapter 16: Deliverance -- Chapter 17: Hidden -- Chapter 18: The battle inside -- Chapter 19: Letting go -- About the author.
Book 1 of the SPRG Trilogy
Layout by Rey de Guzman, Layout Assistant: Angie Espuerta.
Keywords: Parapsychology -- Juvenile literature; Supernatural; Psychic ability